The influence of ratio and allometric scaling procedures for normalizing upper body power output in Division I collegiate football players - Thompson, B. J.; Smith, D. B.; Jacobson, B. H.; Fiddler, R. E.; Warren, A. J.; Long, B. C.; O'Brien, M. S.; Everett, K. L.; Glass, R. G; Ryan, E. D. (The Journal of Strength and Conditioning Research, 2010)
The purpose of the present study was to examine the differences in upper body power output among lineman and nonlineman division I collegiate football players and to examine the influence of 2 normalization procedures: (a) simple ratio scaling and (b) standardized allometric scaling. Ten lineman (mean ± SD: age = 19.3 ± 1.6 years; height = 187.7 ± 4.7 cm; mass = 127.7 ± 13.3 kg) and 14 nonlineman (19.6 ± 1.4 years; 181.8 ± 5.2 cm; 92.3 ± 10.6 kg) performed a multiple repetition bench press power test at 50% of their 1 repetition maximum. Peak power (PP) was determined from a Tendo weightlifting analyzer that was attached to the barbell. The PP values were then analyzed under 3 conditions that included: (a) no scaling (absolute values), (b) ratio scaling (PP body mass-1), and (c) allometric scaling (PP body mass-0.67). The results indicated that the larger lineman demonstrated greater absolute PP values (p = 0.02); however, ratio scaling favored the smaller nonlineman group (p = 0.04). There were no differences in PP values between positions after the standardized allometric scaling procedure (p = 0.60). These findings indicated that the standardized allometric scaling procedure may be a more effective method for normalizing PP values among elite division I collegiate football players.